2000
DOI: 10.1091/mbc.11.12.4259
|View full text |Cite
|
Sign up to set email alerts
|

Exocyst Is Involved in Cystogenesis and Tubulogenesis and Acts by Modulating Synthesis and Delivery of Basolateral Plasma Membrane and Secretory Proteins

Abstract: Epithelial cyst and tubule formation are critical processes that involve transient, highly choreographed changes in cell polarity. Factors controlling these changes in polarity are largely unknown. One candidate factor is the highly conserved eight-member protein complex called the exocyst. We show that during tubulogenesis in an in vitro model system the exocyst relocalized along growing tubules consistent with changes in cell polarity. In yeast, the exocyst subunit Sec10p is a crucial component linking polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
167
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 146 publications
(182 citation statements)
references
References 91 publications
(92 reference statements)
14
167
1
Order By: Relevance
“…Branching morphogenesis of tubular epithelium is a common and important feature of vertebrate organogenesis [1,22,32]. The MAPK/ERK pathway, which is downstream of receptor tyrosine kinases, leads to the phosphorylation, and hence activation, of ERK and has been shown to be important in branching morphogenesis in several systems, including the Drosophila trachea [20] and murine salivary gland [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Branching morphogenesis of tubular epithelium is a common and important feature of vertebrate organogenesis [1,22,32]. The MAPK/ERK pathway, which is downstream of receptor tyrosine kinases, leads to the phosphorylation, and hence activation, of ERK and has been shown to be important in branching morphogenesis in several systems, including the Drosophila trachea [20] and murine salivary gland [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant HGF at 100 ng/ml was added to the basolateral compartment of MDCK cell monolayers following a 1 h pretreatment either with or without U0126 (Promega) or PD098059 (Sigma), both inhibitors of MEK, at 10 μM and 50μM respectively. HGF at 100 ng/ml has been shown to induce tubulogenesis in MDCK cells [1,19]. Recombinant human HGF was generously provided by the late R. Schwall (Genentech, South San Francisco).…”
Section: Mdck Culture Hgf Treatment and Rna Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…LDLR fusion was shown at this site by time-lapse confocal microscopy (Kreitzer et al, 2003), and Shrew-1 and VSV-G fusion was found at this site by tannic acid-blocking experiments (Polishchuk et al, 2004;Jakob et al, 2006). In polarized MDCK cells, the Sec6/8 complex is recruited to (Yeaman et al, 2004) and localized at the apical junctional complex along the lateral membrane (Grindstaff et al, 1998;Lipschutz et al, 2000), which is recognized to be an area of active exocytosis (Kreitzer et al, 2003). We previously reported that Naked2-associated vesicles accumulated asymmetrically at the basolateral corner of MDCK cells stably expressing myristoylation-deficient G2A Naked2.…”
Section: Naked2-coated Vesicles Target Initially To the Lower Portionmentioning
confidence: 95%